(894) دراسة فى التخطيط الاشتراكى - السياسة التحويلية بجمهورية بولندا الشعبية - دراسة تحليلية A Study in Socialist Planning - Changing Politics in the Republic of Poland - A Popular Analytical Study - السيد, عاطف (معهد التخطيط القومى, 2024)
تناولت الدراسة السياسة التمويلية في الدول الاشتراكية، مع التركيز على بولندا كنموذج، حيث شهدت تغييرات كبيرة مرتبطة بالتحول بين المركزية واللامركزية. في الفترة التي أعقبت الحرب العالمية الثانية حتى عام 1948، تركزت الجهود على إعادة البناء من خلال خطة ثلاثية (1947-1949)، واتسمت السياسة المالية خلال هذه الفترة بطابع اللامركزية الواسعة. لاحقًا، تطورت السياسة التمويلية لتصبح أداة لتنفيذ التوجهات التخطيطية، مستجيبةً للتغيرات السياسية والاقتصادية للدولة. وأكدت الدراسة على أهمية السياسة التمويلية في تحقيق التوازن بين الحاجات النقدية والتنمية الاقتصادية ضمن إطار المركزية الديمقراطية. / / The study addresses financial policy in socialist countries, focusing on Poland as a case study, where significant shifts occurred between centralization and decentralization. From the post-World War II period until 1948, efforts were concentrated on reconstruction through a three-year plan (1947-1949), characterized by extensive financial decentralization. Subsequently, financial policy evolved into a tool for implementing planning directives, adapting to the political and economic changes within the state. The study highlights the role of financial policy in balancing monetary needs with economic development under the framework of democratic centralism